The Effect of Cooking Treatment on Antioxidant Activity in Soybean Tempeh - Yulianti Annisa Safitri; Agustina L. N. Aminin; Nies Suci Mulyani (Chemistry Department, Faculty of Sciences and Mathematics, Diponegoro University, 2022)
Indonesian people consume tempeh through various processing methods. Food processing by cooking has been reported to reduce the bioactive capacity contained in food ingredients. This study investigated the effects of food processing (frying, steaming, roasting, sautéing, and boiling) on antioxidants in soybean tempeh. The antioxidant activity of processed tempeh was measured using DPPH and reducing power methods. The results showed that the highest inhibition activity of the processed tempeh was achieved by roasting and boiling (40%). The roasting method yielded tempeh with the highest total phenolic and flavonoid content. Thus, the cooking method considerably influences the antioxidants contained in tempeh. The findings showed that tempeh processed through roasting and boiling has the highest antioxidant activity. The total phenolic and flavonoid profiles are not in line with antioxidant activity, which indicates that the contributors to antioxidant activity are not only phenolic compounds. The increase in antioxidant activity in soybean tempeh is suspected to be influenced by the non-phenolic bioactive peptide compounds found in tempeh.